Towards empowering zakat recipients: an assessment on effectiveness of zakat institutions from the zakat recipients' perspective - Abd. Wahab, Norazlina; Alam, Md Mahmudul; Al Haq, Ashraf; Hashim, Suraiya; Zainol, Zairy (Advance Scientific Research, 2020)
This study aims to investigate the effectiveness of zakat institutions from the zakat recipients’ perspective. Researchers opine that empowering is a matter of utmost importance in order to ensure recipients are self-sufficient, self-reliant and can withstand any hardship come it may. Therefore the zakat authorities need to safeguard a robust empowerment regime and for that reason the assessment of that performance may require a newer dimensional approach where ‘the recipients’ who are the main stakeholders do evaluate the contributory performative assessment through the main four perspectives as enshrined by the Balanced Scorecard technique which include financial effectiveness, customer effectiveness, internal effectiveness and learning & growth effectiveness. Hence, the goal is to investigate the effectiveness of zakat institutions of Kedah, Malaysia in particular. A total of 427 responses received, where Partial Least Squares approach was employed as the main data analysis of this study. The research identified that all the four components are interlinked and need a coherent addressing in terms of zakat recipients’ upliftment. The recipients did put emphasis on the priority of the financial effectiveness, but in a non-profit environment where the customer effectiveness is vital, may require the service enhancement along with putting the emphasis on learning and making certain systematic rejuvenation of the processes, as well as the planned financial decision to make effects conducive to empowerment of the recipients.